Quantitative study on the impact of perceived corporate social responsibility on employee performance at plant protection companies in the Mekong Delta, Vietnam - Phước, Nguyễn Tấn; Huân, Đào Duy; Thảo, Nguyễn Thị Phương (Edelweiss Applied Science and Technology, 2024)
This article presents the results of a formal quantitative survey (Main Study or Official Survey) on the impact of Corporate Social Responsibility Awareness on Employee Performance at plant protection products manufacturing enterprises in the Mekong Delta, Vietnam. The objective is to examine the impact of Perceived Corporate Social Responsibility (PCSR) on employee performance (EP), with the mediating role of organizational trust (OT) and the moderating role of organizational reputation (OR). The Main Study with 385 samples, used SPSS and AMOS to test Cronbach’s Alpha, EFA, CFA and SEM models. The results of the impact coefficients showed that PCSR positively affects EWR with OT as the mediator, and OR as the moderator of this relationship. The coefficients obtained prove that the research hypothesis is appropriate. The research results also provide useful information for managers to better understand the impact of PCSR on employee performance, thereby making appropriate strategic adjustments to business goals. Due to the limited space and sample size, this is a limitation of the study.